The weight of the uniform: The perception of Military Police Officers in a unit in Western Paraná regarding the inherent power of the profession (Research, Society and Development, 2025)
Abuse of authority is a crime regulated by Law 13,869/2019, which describes acts of abuse of power that may be committed by public servants, including military police officers. The number of reports of such cases, registered solely through the Dial 100 hotline in 2019, amounted to 1,486, demonstrating its high incidence. The present research aims to investigate the perception of military police officers from a unit in western Paraná regarding the power inherent to the profession, taking as a starting point the officers’ views on power relations with civil society, as well as on violence and the use of force. The study was conducted with four military police officers and analyzed through content analysis, revealing three main recurring topics in the officers’ discourse: the control of society and police identity; the progressive use of force and the naturalization of violence; and police authority and power relations. From the discussion presented by the researchers, it is evident that the themes of violence, power, and authority are closely intertwined when it comes to the Military Police. As these themes are influenced by culture, they must be understood as dynamic concepts, requiring constant reassessment.